Selective Janus Kinase 1 Inhibition Is a Promising Therapeutic Approach for Lupus Erythematosus Skin Lesions - Fetter, Tanja; Smith, Paul; Guel, Tugce; Braegelmann, Christine; Bieber, Thomas; Wenzel, Joerg (Frontiers in Immunology, 2020)
Background: Cutaneous lupus erythematosus (CLE) is an interferon (IFN) -driven autoimmune skin disease characterized by an extensive cytotoxic lesional inflammation with activation of different innate immune pathways. Aim of our study was to investigate the specific role of Janus kinase 1 (JAK1) activation in this disease and the potential benefit of selective JAK1 inhibitors as targeted therapy in a preclinical CLE model. Methods: Lesional skin of patients with different CLE subtypes and healthy controls (N=31) were investigated on JAK1 activation and expression of IFN-associated mediators via immunohistochemistry and gene expression analyses. The functional role of JAK1 and efficacy of inhibition was evaluated in vitro using cultured keratinocytes stimulated with endogenous nucleic acids. Results were confirmed in vivo using an established lupus-prone mouse model. Results: Proinflammatory immune pathways, including JAK/STAT signaling, are significantly upregulated within inflamed CLE skin. Here, lesional keratinocytes and dermal immune cells strongly express activated phospho-JAK1. Selective pharmacological JAK1 inhibition significantly reduces the expression of typical proinflammatory mediators such as CXCL chemokines, BLyS, TRAIL and AIM2 in CLE in vitro models and also improves skin lesions in lupus-prone TREX1-/- -mice markedly. Conclusion: IFN-associated JAK/STAT activation plays a crucial role in the pathophysiology of CLE. Selective inhibition of JAK1 leads to a decrease of cytokine expression, reduced immune activation and decline of keratinocyte cell death. Topical treatment with a JAK1-specific inhibitor significantly improves CLE-like skin lesions in a lupus-prone TREX1-/- -mouse model and appears to be a promising therapeutic approach for CLE patients.